2009
DOI: 10.1364/oe.17.001291
|View full text |Cite
|
Sign up to set email alerts
|

Photostimulation of astrocytes with femtosecond laser pulses

Abstract: The involvement of astrocytes in brain functions rather than support has been identified and widely concerned. However the lack of an effective stimulation of astrocytes hampers our understanding of their essential roles. Here, we employed 800-nm near infrared (NIR) femtosecond laser to induce Ca2+ wave in astrocytes. It was demonstrated that photostimulation of astrocytes with femtosecond laser pulses is efficient with the advantages of non-contact, non-disruptiveness, reproducibility, and high spatiotemporal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 38 publications
0
41
0
3
Order By: Relevance
“…The fluorescence intensity, indicating relative calcium ion concentration in the cell, increases with time after the irradiation. Similar, but faster, calcium ion activity evoked by femtosecond laser irradiation was reported in nerve cells (Smith et al, 2005) and astrocytes (Zhao et al, 2009) The underlying mechanism of intracellular calcium ion concentration rise was studied (Iwanaga et al, 2005;Iwanaga et al, 2006a). Calcium ion stores such as endoplasmic reticulum (ER) and mitochondria play a central role in the phenomena.…”
Section: Nonlinear Fast and Local Approach To Optical Pacingmentioning
confidence: 76%
“…The fluorescence intensity, indicating relative calcium ion concentration in the cell, increases with time after the irradiation. Similar, but faster, calcium ion activity evoked by femtosecond laser irradiation was reported in nerve cells (Smith et al, 2005) and astrocytes (Zhao et al, 2009) The underlying mechanism of intracellular calcium ion concentration rise was studied (Iwanaga et al, 2005;Iwanaga et al, 2006a). Calcium ion stores such as endoplasmic reticulum (ER) and mitochondria play a central role in the phenomena.…”
Section: Nonlinear Fast and Local Approach To Optical Pacingmentioning
confidence: 76%
“…Iwanaga et al used two different extracellular solutions either containing Ca 2+ chelator EGTA or inhibitor for cellular sensor to shockwave-based mechanical effects to demonstrate that femtosecond laser-induced cellular calcium increase was due to the leaking of Ca 2+ through the destruction of intracellular Ca 2+ stores [97]. Zhao et al directly photodisrupted plasma membrane of astrocytes to make a temporary hole for extracellular calcium influx [98]. And Zhou et al reported that calcium increase in living olfactory ensheathing cells by 1 kHz femtosecond laser was related with shockwave-induced mechanical force [94].…”
Section: Biological Mechanism Studymentioning
confidence: 99%
“…A lot of cell processes are activated simultaneously and some of them can feedback to contribute to more Ca 2+ release, like ROS generated by two-photon excitation of endogenous absorbers [103] and/or oxidative stress to ER [104]. Interestingly, intercellular Ca 2+ wave propagation among excitable cells or non-excitable cells was also observed after the intracellular Ca 2+ release by femtosecond laser [6,98,105]. He et al proposed three possible mechanisms: 1) Ca 2+ signaling molecules such as ATP was released from the photostimulated cell and diffused away to excite Ca 2+ release in surrounding cells; 2) mechanical stress of shear flow by the plasma generation impacted surrounding cells to activate the release of Ca 2+ ; 3) mechanical stress of acoustic wave stimulated Ca 2+ release along its propagation [106].…”
Section: Biological Mechanism Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies of femtosecond stimulation of neurons [10][11][12][13][14][15][16][17][18][19][20] have proposed essentially two mechanisms induced by the laser: photo-disruption and photo-poration, where the transition from a dominant disruption mechanism to a dominant poration mechanism occurs at laser power densities ~ 5×10 11 W/cm 2 (e.g. ~35mW of 800nm, 100fs, 80MHz light focused with a 0.9 NA objective).…”
Section: Optical Stimulation Of Dissociated Cortical Neuronsmentioning
confidence: 99%